Structural and optical properties of nc-Si in SiOxNy matrix deposited by laser ablation for optoelectronic applications. (1st March 2019) - Camps, Enrique; Campos-Gonzalez, E.; Restrepo, Johans; Dutt, A.; Santana, G.
Abstract: In this work, we show the development of SiOx Ny (silicon oxynitride) thin films using the laser ablation technique. Instead of commonly used precursor materials SiH4 and NH3 or N2, hereby, we report the deposition using crystalline silicon targets and N2 precursors. The experiment was carried out in such a way that we can eradicate the drawback of hydrogen concentration in the thin films (due to silane precursor) and finally, adequate deposition conditions were found which allowed obtaining the material with suitable optoelectronic properties. Numerous experiments varying the deposition pressure (0.4–6 Pa) were carried out making possible the formation of different kinds of the stoichiometry of the material. For one set of thin films (lower pressure), silicon rich silicon-oxynitride thin films (SRSON) were obtained, whereas, for the other half (higher pressure) it was oxygen-rich silicon oxynitride (ORSON) kind of stoichiometry. Fourier transform infrared spectroscopy (FTIR) shown the dominance of Si-N bonds for the samples deposited at lower pressure, whereas, for the samples deposited at higher pressure shift in the absorption bands towards Si-O bonds was observed. For the middle-pressure range ;(0.8–2 Pa) depending on the composition of SiOx Ny thin films, a band gap variation from 2.08 eV to 4.36 eV was obtained. The same could be correlated with the Si, N and O ratios in the deposited thin films. From the XPS analysis, it was found that the Si content was found to be reduced, whereas, N content was found to be varying randomly as an effect of an increase in the pressure. Lately, it also shown an overall increase in the O concentration. For the same range of pressure value (0.8–2 Pa), Raman, X-ray diffraction (XRD) and HRTEM analysis illustrated the formation of crystalline silicon nanoparticles from the as-deposited thin films. Overall, confirmation of Si nanoparticles embedded in an amorphous matrix of SiOx Ny can be established from these analyses. Photoluminescence (PL) spectra also demonstrated the visible emission which remarks the quality of material and its tendency for the optical applications. Intense and homogenous PL was observed for samples grown at 2 Pa. Using unique deposition method presented in this manuscript with a great control over the composition and hence, on the optoelectronic properties of Si related thin films can be used for the future optoelectronic applications.